The 2nd International Conference of Medical Goes Public (ICON MEGOPIC 2025), 3rd to 4th September 2025 (Malaysian Journal of Public Health Medicine, 2025)
The 2nd International Conference of Medical Goes Public (ICON MEGOPIC 2025), 3rd to 4th September 2025